Characterization of Corrosive Bacterial Consortia Isolated from Water in a Cooling Tower. (3rd March 2014) - Aruliah, Rajasekar; Ting, Yen-Peng
Abstract : An analysis of a culturable corrosive bacterial community in water samples from a cooling tower was performed using traditional cultivation techniques and its identification based on 16S rRNA gene sequence. Seven aerobic bacterial species were identified: Pseudomonas putida ARTYP1, Pseudomonas aeruginosa ARTYP2, Massilia timonae ARTYP3, Massilia albidiflava ARTYP4, Pseudomonas mosselii ARTYP5, Massilia sp. ARTYP6, and Pseudomonas sp. ARTYP7. Although some of these species have commonly been observed and reported in biocorrosion studies, the genus Massilia is identified for the first time in water from a cooling tower. The biocorrosion behaviour of copper metal by the new species Massilia timonae ARTYP3 was selected for further investigation using a weight loss method, as well as electrochemical and surface analysis techniques (SEM, AFM, and FTIR). In contrast with an uninoculated system, thin bacterial biofilms and pitting corrosion were observed on the copper metal surface in the presence of M. timonae . The use of a biocide, bronopol, inhibited the formation of biofilm and pitting corrosion on the copper metal surface.